Yellow Striped Giraffehopper Spartolus pugionatus Stål, 1877 comb. resurr. (Tetrigidae: Ophiotettegini) inhabits Mindanao Island of the Philippines’ archipelago - Mohagan, Alma B.; Leańo, Emmanuel P.; Melencion, Merced G.; Patano, Romeo R. Jr.; Hongco, Aldrin L.; Amoroso, Victor B. (Zootaxa, 2020)
The genus Threciscus Bolívar, 1887 (Tetrigidae: Ophiotettigini) was a monotypic genus endemic for the Philippines and included only T. pugionatus (Stål, 1877). Here, after examination of series of specimens, we conclude that T. pugionatus is morphologically close to Spartolus tricostatus Bolívar, 1887 and we move the species back to the genus Spartolus Stål, 1877, giving it back combination Spartolus pugionatus comb. resurr. The species was originally described from a single female (holotype) from Semper’s collection, and, as most of specimens from that collection, lacked locality data. It is only known that Semper’s material originates from the Philippines. In this study, the very first annotated records of the species are presented. It inhabits central part of the island of Mindanao, mountainous tropical rainforests. We provide images of specimens under stereomicroscope and in natural habitat, brief morphological description, as well as updated distribution map. The species is easily recognizable by its coloration, lack of wings, prolonged head, foliaceous palpi and lateral spines. Furthermore, we report new localities for Arulenus miae Skejo et Caballero, 2016.